An essence of public government, its subjects and functions - Malkhaz Chakhnashvili (IBSU Scientific Journal (IBSUSJ), 2010)
In Administrative Law of Georgia Public government is defined as activity of executory ordering bodies, therefore, area of operation for the public government is limited with the share of functioning of executive branch. We think that such conception is not correct and does not reflects real interconnections between branches of state machinery government (management, administration) is not a type of activity of certain group of state bodies, as it is understood in Georgian Administrative law, but systematic method of solution of problems and functional tasks, faced to the any branch of state power. So, the frame of public government should be expended and define that Public Government should be diversified into three types: Representative, Executive and Judicial Government. All of them have certain vertical of structural units of nine levels in case of executive government, two levels of representative and four levels of judicial government with their functionaries. Subjects of public government have same stages of activity, sources of financing, order of classification but different diversification indication in the structure of state machinery. Beside executive, representative and judicial bodies we think that a new category of subjects- namely special subject of public government have to be distinguished because the President, Parliament and Constitutional court have mutual integrated rights in different spheres of the public government. Upon a new approach to the concept of public government in Georgian Administrative law the definitions of representative, executive, judicial and public government are formulated.
Keywords: 330; theory of administrative law; Georgia